Nine perfect strangers - Moriarty, Liane; Lee, Caroline 1953- (New York, NY Macmillan Audio, 2018)
At a remote health resort, nine strangers and their enigmatic host become subjects of interest to former best-selling novelist Frances Welty, who develops uncomfortable doubts about the resort's real agenda.
Title from container.
Compact discs.
Read by Caroline Lee.
107127
Keywords: Novelists -- Fiction; Health resorts -- Fiction; Strangers -- Fiction; Interpersonal relations -- Fiction; City dwellers -- Fiction; Strangers -- Fiction; Interpersonal relations -- Fiction; Fiction; Contemporary Women -- Fiction; Family Life -- Fiction; Thrillers -- Fiction -- Domestic; Novelists; City dwellers; Health resorts; Interpersonal relations; Strangers; Audiobooks; Fiction; Psychological fiction; Novels; Thrillers (Fiction); Suspense fiction; Fiction